2020
DOI: 10.3390/ma13071723
|View full text |Cite
|
Sign up to set email alerts
|

Phase Studies of Additively Manufactured Near Beta Titanium Alloy-Ti55511

Abstract: The effect of electron-beam melting (EBM) and selective laser melting (SLM) processes on the chemical composition, phase composition, density, microstructure, and microhardness of as-built Ti55511 blocks were evaluated and compared. The work also aimed to understand how each process setting affects the powder characteristics after processing. Experiments have shown that both methods can process Ti55511 successfully and can build parts with almost full density (>99%) without any internal cracks or delaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, this composition has been employed for plenty of aviation purposes, such as load‐bearing parts, landing gears, and frames. [ 122 ] In 2020, Maimaitiyili et al [ 123 ] examined Ti‐55 511 processed via the L‐PBF and EBM methods. It was demonstrated that both processes could produce Ti55511 and attain virtually full density with limited porosity.…”
Section: Titanium Alloys Processabilitymentioning
confidence: 99%
“…Therefore, this composition has been employed for plenty of aviation purposes, such as load‐bearing parts, landing gears, and frames. [ 122 ] In 2020, Maimaitiyili et al [ 123 ] examined Ti‐55 511 processed via the L‐PBF and EBM methods. It was demonstrated that both processes could produce Ti55511 and attain virtually full density with limited porosity.…”
Section: Titanium Alloys Processabilitymentioning
confidence: 99%
“…This results in major residual stresses in the L-PBF material which generally requires post stress relieving heat treatment in contrast to E-PBF material which is constantly annealed throughout the PBF process. Furthermore, E-PBF material has a considerably larger surface roughness compared to L-PBF which is mainly attributed to the larger layer thickness and larger particle size for the E-PBF process [18], see Table 1.…”
Section: E-pbf Compared To L-pbf Processmentioning
confidence: 99%
“…While the AM of these materials has been largely successful, near-beta alloys such as Ti-5553 and Ti-55511 exhibit superior fracture toughness, are readily heat treatable, and are gaining popularity in the aerospace sector [13,14]. Accordingly, open literature on the development of AM techniques for near-beta Ti alloys is starting to emerge [5,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%